A fossil protein chimera; difficulties in discriminating dinosaur peptide sequences from modern cross-contamination. Issue 1855 (31st May 2017) - Buckley, Michael; Warwood, Stacey; van Dongen, Bart; Kitchener, Andrew C.; Manning, Phillip L.
Abstract : A decade ago, reports that organic-rich soft tissue survived from dinosaur fossils were apparently supported by proteomics-derived sequence information of exceptionally well-preserved bone. This initial claim to the sequencing of endogenous collagen peptides from an approximately 68 Myr Tyrannosaurus rex fossil was highly controversial, largely on the grounds of potential contamination from either bacterial biofilms or from laboratory practice. In a subsequent study, collagen peptide sequences from an approximately 78 Myr Brachylophosaurus canadensis fossil were reported that have remained largely unchallenged. However, the endogeneity of these sequences relies heavily on a single peptide sequence, apparently unique to both dinosaurs. Given the potential for cross-contamination from modern bone analysed by the same team, here we extract collagen from bone samples of three individuals of ostrich, Struthio camelus . The resulting LC–MS/MS data were found to match all of the proposed sequences for both the original Tyrannosaurus and Brachylophosaurus studies. Regardless of the true nature of the dinosaur peptides, our finding highlights the difficulty of differentiating such sequences with confidence. Our results not only imply that cross-contamination cannot be ruled out, but that appropriate measures to test for endogeneity should be further evaluated.